2015
DOI: 10.5812/ijp.176
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signs and Symptoms and Laboratory Findings of Methadone Poisoning in Children

Abstract: Background:Poisoning accounts for about 7% of all accidents in children under 5 years and is implicated in over 5% of all childhood deaths in developing countries.Objectives:Due to the potential risks of methadone poisoning in children and increased cases of methadone poisoning among Iranian children, this study was conducted to investigate the clinical signs and symptoms and laboratory findings of methadone toxicity in children.Patients and Methods:The present retrospective, descriptive, cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…The gastrointestinal symptoms were comparable to those reported for methadone poisoning in a previous Iranian study [16]; however, respiratory depression was less common in tramadol poisoning. Hypotension was reported in methadone poisoning [17], but we did not encounter any casses of hypotension in our study of tramadol-poisoned patients. The prevalence of tachycardia in our patients was similar to that in dextromethorphan-poisoned patients reported in a large study in the USA; however, the rate of hypertension in tramadol-poisoned patients in the current study was higher than that in dextromethorphan-poisoned patients [14].…”
Section: Discussionmentioning
confidence: 49%
“…The gastrointestinal symptoms were comparable to those reported for methadone poisoning in a previous Iranian study [16]; however, respiratory depression was less common in tramadol poisoning. Hypotension was reported in methadone poisoning [17], but we did not encounter any casses of hypotension in our study of tramadol-poisoned patients. The prevalence of tachycardia in our patients was similar to that in dextromethorphan-poisoned patients reported in a large study in the USA; however, the rate of hypertension in tramadol-poisoned patients in the current study was higher than that in dextromethorphan-poisoned patients [14].…”
Section: Discussionmentioning
confidence: 49%
“…Methadone is a dangerous drug for children, as very small amounts of it can cause various disorders including: 1) central nervous system symptoms including loss of consciousness, miosis, delirium, and convulsion; 2) respiratory symptoms such as apnea; 3) skin symptoms; dermatologic signs and symptoms including hair loss; 4) cyanosis, 5) cardiovascular difficulties including bradycardia, bradyarrhythmia, hypotension, cardiac arrest, filiform pulse, peripheral circulation failure, prolonged corrected QT interval, and risk of torsades de pointes; 7) metabolic complications including respiratory and metabolic acidosis; 8) hypercapnia, hyponatremia, hypoxia, hypoxemia, and hypoglycemia; and 9) death (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the facts that younger family members of methadone abusers are at a higher risk for accidental or intentional intoxication and the seriousness of clinical consequences for poisoning with methadone dosage forms in children, the number of reported studies with a demographic and clinical description of poisoning with methadone in the pediatric population is limited. [51213141516] Sharif et al . in a study conducted in Iran have reported clinical complications in almost half (48.3%) of the children with acute methadone toxicity, which is in contrast to our study with a 7.6% of complication during treatment.…”
Section: Discussionmentioning
confidence: 99%